Peran Dukungan Kelompok dalam Menjaga Kualitas Hidup Pasien Kanker Payudara: Studi Kasus Pada Share and care Community di Kota Medan) - Nur Fitri Ramadani Siregar; Erni Asneli Asbi (LPPM UNISDA, 2026)
This study discusses the role of group support in maintaining the quality of life of breast cancer patients in the Share and Care Community in Medan City. Breast cancer does not only affect patients' physical condition, but also influences their psychological, social, and spiritual aspects, so that non-medical support becomes important in accompanying the treatment process and maintaining a comprehensive quality of life. This study aims to describe the forms of group support, analyze its role in maintaining the quality of life of breast cancer patients, and identify the obstacles and challenges faced by the Share and Care Community. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation with informants selected purposively. The results show that the most prominent form of group support is the support group, manifested through emotional support, sharing experiences, providing information, practical assistance, and a sense of togetherness among fellow survivors. This group support plays a role in maintaining patients' quality of life from a biopsychosocial-spiritual perspective, helping patients become more prepared to undergo treatment, emotionally stronger, socially connected, and able to gain hope and meaning in facing the illness. The study also found that the implementation of group support still faces challenges, especially in the continuity of activities, limited community resources, spiritual strengthening that still tends to be oriented toward a particular religion, the need for the involvement of medical social workers, and the need for collaboration with relevant parties.